Ультраструктурні зміни кортикотропних клітин передньої частки аденогіпофіза за умов дії червоного шламу та засобів їх корекції - Борецький, Геннадій; Boretsky, Genady (Східноєвропейський національний університет імені Лесі Українки, 2017)
Отримано нові дані відносно характеру й динаміки ультраструктурних змін у кортикотропних клітинах аденогіпофіза за умов тривалої дії на організм червоного шламу. Установлено залежність змін структури й функції кортикотропів від тривалості дії червоного шламу у тварин різного віку. Запропоновано спосіб корекції дії червоного шламу на кортикотропи з використанням альфа-токоферолу. New data concerning the character and the dynamic of the ultrastructural changes of adenohypophysis corticotrophic cells under the prolonged influence of the red mud to the body has been received with the help of modern methods (electronic microscopy, optical Image Analysis morphometry). The correction method of the red mud influence on the corticotrops with the alpha-tocopherol exploitation has been suggested. It has been established that rats staying under the red mud influence during 14 days leads to the intensification of the corticotrophic cells function, which is accompanied by the increasing of chromatin in the corticotrophic nuclei of middle area, by the increasing of mitochondria in cytoplasm, secretory granules and their activity index, in the comparison with the test animals. However, it is observed the signs of dystrophic changes in individual corticotrophic cells, the destructive reconstructions in the nucleus structures (hyperchromic, bullate and edema nuclei) and in the membrane cytoplasm structures (endoplasmic reticulum vacuolization with the partial destruction of its membranes and hollow formation, mitochondrial matrix hardening). Ultrastructural changes of corticotrophic cells on 45-days experimental rats point out the evidence of weakening function, which occurs against the background of decrease of chromatin, mitochondria, secretory granules quantity. Expressed dystrophic changes and destructive rebuildings determine in the ultrastructural corticotrophic organization both in the nucleus structures and in the cytoplasm cell membranes and in the endothelium hemocapillar bed, which surround these cells.Ultra structural rebuildings of corticotrophic cells on 180-days experimental rats under the prolonged influence of the red mud are evidence of the suppression continuation of their functions, which are accompanied by destructively dystrophic changes in their structure and conform to the stage of exhaustion general adaptation syndrome. Нerewith, ultrastructural signs of mild activation of intracellular reparative regeneration are determined among certain corticotrophic cells (size and number increasing of the Golgi complex elements and granular endoplasmic reticulum, increasing the number of young forms of mitochondria, free ribosome and polyribosome). Alpha-tocopherol usage under the influence of red mud contributes to the weakening of its toxic effect and force of the stress response of the corticotrophic cells which acquires the expressiveness with the age and the maturity of the animals and the term of alpha-tocopherol influence. There are the normalization marks in the ultrastructural organization of corticotrophic cells indicating a positive alpha-tocopherol impact on the recovery of the corticotrophic cells ultrastructures
Ultrastructural Changes of Adenohypophysis Corticotrophic Cells Under the Influence of Red Mud and Their Correction Methods
Keywords: аденогіпофіз; червоний шлам; альфа-токоферол; кортикотропні клітини; ультраструктура; adenohypophysis; alpha-tocopherol; red mud; ultrastructure; corticotropic cells